Pelvic venous and pulmonary artery extension in low-grade endometrial stromal sarcoma: a case report - Li, Yi-Ling; Sun, Xin; Ye, Ming-Zhu; Wang, Chen; Cheng, Hui; Huang, Shan-Yu; Xi, Xiao-Xiao (Frontiers in Oncology, 2025)
BackgroundVascular invasion is a hallmark of low-grade endometrial stromal sarcoma (LG-ESS), typically presenting a tumor thrombus within the parametrial vessels. However, extension of tumor thrombus into major vessels such as pulmonary artery is extremely rare. This case report presents an unusual manifestation of LG-ESS with intravascular tumor thrombi extending to the pelvic venous and pulmonary artery, highlighting the diagnostic challenges and clinical implications of vascular involvement.Case presentationA 42-year-old female presented with prolonged menstruation. Imaging examination initially suggested multiple uterine fibroids, and hysteroscopic resection of a polypoid lesion revealed stromal hyperplasia, raising suspicion of an endometrial stromal nodule. One year later, the patient developed a pulmonary embolism and imaging showed disease progression. A hysteroscopic biopsy confirmed the diagnosis of LG-ESS. She subsequently underwent total abdominal hysterectomy (TAH) with bilateral salpingo-oophorectomy (BSO) and venous thrombectomy. Histopathological examination revealed LG-ESS with deep myometrial invasion and extensive intravascular tumor thrombus extending into the pelvic veins. The pathological stage was pIIA(FIGO). Postoperative chemotherapy with liposomal doxorubicin was administered, and follow-up pulmonary computed tomography angiography showed resolution of the emboli. No recurrence was noted at the six-month follow-up.ConclusionsThis case highlights the diagnostic complexity of LG-ESS due to its nonspecific clinical presentation and imaging findings, especially in early stages. Rare vascular involvement, including pulmonary artery tumor embolism, poses a risk of misdiagnosis and highlights the importance of thorough histopathological evaluation. Early hysteroscopic intervention, accurate pathological assessment, and individualized adjuvant therapy are critical for optimizing outcomes in patients with LG-ESS exhibiting vascular extension. Informed consent for publication was obtained from the patient.